1994
DOI: 10.1007/bf02444621
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of monoclonal antibodies obtained by immunization of mice with trypsin-treated group a streptococcus culture

Abstract: Hybridomas producing monoclonal antibodies intensively reacting with group A streptococcus antigens in enzyme immunoassay were obtained as a result of immunizing mice with pepsin-treated cultures of group A streptococcus. All antibodies were referred to class M immunoglobulins. The reactions of monoclonal antibodies were completely inhibited by the pepsin-treated culture of group A streptococcus. The degree of inhibition with A-polysaccharide was lower, being 17.5 to 50.0 in different monoclonal antibodies. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…It was previously shown that these antibodies are directed to organ-specific myocardial antigens common for animals of different species (rabbit, mouse, ox, etc. ), that is, they were autoantibodies [1,3]. Hence, immunization of animals according to the above protocol results in production of not only antibodies to streptococcal antigens, but also autoantibodies.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It was previously shown that these antibodies are directed to organ-specific myocardial antigens common for animals of different species (rabbit, mouse, ox, etc. ), that is, they were autoantibodies [1,3]. Hence, immunization of animals according to the above protocol results in production of not only antibodies to streptococcal antigens, but also autoantibodies.…”
Section: Resultsmentioning
confidence: 97%
“…The mice were intraperitoneally immunized with the vaccine in ascending doses during 3 weeks (3 consecutive days in each week): 1 billion bacterial cells/injection on week 1, 2 billions on week 3, and 3 billions on week 3. Immunization of animals (rabbits, mice) according to this protocol leads to the formation (in addition to antibodies to streptococcal antigens) of autoantibodies to various tissue antigens, the maximum antibody production was observed on days 7-14 after the last injection of the antigens [1,3]. Autoantibodies to heart tissue antigens were detected in the sera of immune mice by indirect immunofluorescence on bovine heart tissue sections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these and previous [5] studies indicate that A-PS contains at least 4 cross-reacting determinants. The dominant role of rhamnose in this epitopes suggests the presence of cross-reacting determinants common for skin epithelial and thymic antigens in group A streptococci and in other microorganisms, whose polysaccharide contains rhamnose.…”
Section: Resultsmentioning
confidence: 81%
“…Challenge dose (3X10 9 bacterial cells) was injected intravenously on day 25 after the last injection to mice with high anti-A-PS antibody titer. After 2 days splenocytes were fused with murine plasmacytoma cells [5]. Antibodies to A-PS in the sera, supernatants, and aseitic fluids containing MAb were detected by ELISA [7], or agar gel immunodiffusion [2].…”
Section: Methodsmentioning
confidence: 99%